2020
DOI: 10.1111/geb.13244
|View full text |Cite
|
Sign up to set email alerts
|

Search for top‐down and bottom‐up drivers of latitudinal trends in insect herbivory in oak trees in Europe

Abstract: Aim The strength of species interactions is traditionally expected to increase toward the Equator. However, recent studies have reported opposite or inconsistent latitudinal trends in the bottom‐up (plant quality) and top‐down (natural enemies) forces driving herbivory. In addition, these forces have rarely been studied together thus limiting previous attempts to understand the effect of large‐scale climatic gradients on herbivory. Location Europe. Time period 2018–2019. Major taxa studied Quercus robur. Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 88 publications
2
21
0
Order By: Relevance
“…We therefore refrain from putting forth any particular mechanism that may underlay the patterns we observed. However, we speculate that denser tree canopies may have buffered micro-climatic variations (Coley and Barone, 1996;Dale and Frank, 2014;Yamasaki and Kikuzawa, 2003), which may have been particularly favourable to chewing herbivores that are external feeders (Savilaakso et al, 2009) and at the same time unfavorable to leaf-galling herbivores, as they benefit from high temperatures (Valdés-Correcher et al, 2021). Alternatively, top-down forces also vary with local canopy cover and may consequently influence insect herbivory.…”
Section: Effect Of Local Canopy Cover On Herbivorymentioning
confidence: 94%
See 4 more Smart Citations
“…We therefore refrain from putting forth any particular mechanism that may underlay the patterns we observed. However, we speculate that denser tree canopies may have buffered micro-climatic variations (Coley and Barone, 1996;Dale and Frank, 2014;Yamasaki and Kikuzawa, 2003), which may have been particularly favourable to chewing herbivores that are external feeders (Savilaakso et al, 2009) and at the same time unfavorable to leaf-galling herbivores, as they benefit from high temperatures (Valdés-Correcher et al, 2021). Alternatively, top-down forces also vary with local canopy cover and may consequently influence insect herbivory.…”
Section: Effect Of Local Canopy Cover On Herbivorymentioning
confidence: 94%
“…Urbanization and local canopy cover were slightly negatively correlated (Pearson r = -0.38, P < 0.05), and were independent of latitude (Urbanization: Pearson r = 0.02, P > 0.05; Local canopy cover: Pearson r = 0.04, P > 0.05) and climate (Temperature and urbanization: Pearson r = -0.02, P > 0.05; Temperature and local canopy cover: Pearson r = -0.12, P < 0.05; Precipitation and urbanization: Pearson r = 0.03, P > 0.05; Precipitation and local canopy cover: Pearson r = 0.01, P > 0.05). Although latitude was negatively correlated with temperature (Pearson r = -0.76,P < 0.05) and precipitation (Pearson r = -0.70,P < 0.05) which could have caused collinearity issue, a previous study found that climatic variables were better predictors of variation in herbivory and therefore decided to only include climatic variables in the models (Valdés-Correcher et al, 2021).…”
Section: Landscape Characteristics and Climatic Datamentioning
confidence: 99%
See 3 more Smart Citations